2013
DOI: 10.1111/jsbm.12016
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Performance Based on the Lean-Agile Operations and Supplier-Firm Partnership: An Empirical Study on the Garment Industry in Indonesia

Abstract: The purpose of this study is to explore how lean–agile operations and supplier–firm partnership can improve garment small and medium enterprise (SME) supply chain performance. This study is based on cross‐sectional survey research that provides longitudinal evidence to show how lean–agile operations and partnership strategy influence supply chain and garment SME performance. To clarify the relationships among these constructs, structural equation model (SEM) is conducted to examine the model fit and the five h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 39 publications
(108 reference statements)
2
49
0
1
Order By: Relevance
“…Asia, which plays an important role in the global market, occupied only 28% of studies (e.g. , Kumar et al 2006, Lee 1997, Sukwadi et al 2013. Further analysis of the twenty Asian based studies found the majority to be in India.…”
mentioning
confidence: 99%
“…Asia, which plays an important role in the global market, occupied only 28% of studies (e.g. , Kumar et al 2006, Lee 1997, Sukwadi et al 2013. Further analysis of the twenty Asian based studies found the majority to be in India.…”
mentioning
confidence: 99%
“…Furthermore, there is a limited research on role of power in SCP in the context of 17 SMEs (Adams et al, 2012;Sukwadi et al, 2013). Large organizations are often well 18 equipped and prepared to play the power games in their favor.…”
mentioning
confidence: 99%
“…Agribusiness SMEs participate in several interlinked supply chains which make 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 g r i b u s i n e s s i n D e v e l o p i n g a n d E m e r g i n g E 4 supply chain relationships a critical issues for their success (Park and Krishnan, 2001;Adams 1 et al, 2012;Sukwadi et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, due to the competitive market in the garment industry [21], the performance framework should also focus on the agility measures, which were driven by innovative product and unstable demand [22]. On the contrary, the automobile industry's performance rely upon the forecasting accuracy [as a make-to-stock system] and this requires measuring the accuracy of forecasting [23].…”
Section: Supply Chain Performance Managementmentioning
confidence: 99%